Prevention at home in older persons with (pre-)frailty: analysis of participants’ recruitment and characteristics of the randomized controlled PromeTheus trial - Fleiner, Tim; Nerz, Corinna; Denkinger, Michael; Bauer, Jürgen M.; Grüneberg, Christian; Dams, Judith; Schäufele, Martina; Büchele, Gisela; Rapp, Kilian; Werner, Christian (Aging clinical and experimental research, 2024)
The “PromeTheus” trial is evaluating a home-based, multifactorial, interdisciplinary prevention program for community-dwelling (pre-)frail older adults. These individuals often suffer from reduced participation, which can complicate the recruitment and enrollment in a clinical trial.
Gesehen am 13.11.2024